Teachers’ and Students’ Perception on the Use of Cake Application toward Their Speaking Skill On Merdeka Belajar Era (ELT-Lectura, 2023)
The purpose of this research is to understand and describe the perceptions of teachers and students about the use of cake applications on English speaking skills. The method applied in this research is descriptive qualitative which is presented in the form of a proportion diagram. The data collecting technique of this research used observation,questionnaires, and documentation. The researcher did direct observation in SMP Surya Dharma Bandar Lampung both in the class and out class. The questionnairesof this research used the four most alternative answers, namely strongly agree, agree, neutral and disagree. The questionnaires consisted of 10 numbers questions. The documentation technique were the documentation of score English Speaking skill from the English teacher before giving  the cake application. Participants in this research were 40 students of SMP Surya Dharma Bandar Lampung and 10 teachers of SMP Surya Dharma Bandar Lampung. This research used 9th grade class. Based on the research results obtained, it showed that most teachers and students agree with the learning method using the Cake application. The students were more interested in English learning. The students felt enjoy and fun learning English using the Cake application. Therefore, this research found that the variety of teaching method gave positive effect for the students.